ANALISIS PENGARUH KOMUNIKASI DAN INTERAKSI PADA KEGIATAN OUTBOUND TRAINING TERHADAP KERJASAMA PEGAWAI - Muhammad Solkhan (Universitas Merdeka Malang, 2019)
Abstract This study aims to examine whether communication and interaction in outbound training activities affect employee working behavior. The population of this study were employees, practitioners and teachers from several companies and educational institutions in the Malang region, Pasuruan, Mojokerto, Sidoarjo and Surabaya totaling 376 people, who held outbound training activities with the Training Institute and Human Resource Developers (LPP-SDM ) Nabhan Star with a total sample of 79 people. Using classical assumption test analysis, the coefficient of determination and simultaneous and partial testing are then tested by hypothesis. The results of the study explained: 1). Outbound training activities through communication and interaction simultaneously have an effect on employee collaboration behavior. This is evidenced by the results of F-Count of 16,360 with a significance value of 0,000. 2). Outbound training activities through communication have a partial effect on employee collaboration behavior. This is evidenced by the results of t-count of 16,831 with a significance value of 0,000, while the outbound training activities through interaction do not partially affect the employee's cooperative behavior. This is evidenced by the results of t-count of 0.425 with a significance value of 0.672. Keywords: communication, interaction, outbound training, employee collaboration.DOI: https://doi.org/10.26905/nomosleca.v5i2.3441